Manpower Profile of Women Onion Farmers in Tampo Village Anggeraja District Enrekang Regency - Hasridha Riani Sarif; Sulaiman Zhiddiq; Ibrahim Abbas (Universitas Negeri Makassar, 2020)
This study aims to determine: 1) what factors the background of women working on the land of onion, 2) the level of labor welfare of women farmers onion. This includes quantitative empirically descriptive study, with a sample population of 321 cc and 32 cc. Collecting data using observation, interview and documentation. Data analysis using quantitative data analysis techniques persentase.Hasil this study show that: 1) the respondents were generally at the age of 31-40 years, the level of education in general education level of respondents was tammat High School, the number of dependents of respondents generally ranged 3-4 , revenues derived respondents generally around Rp. 1.500.000- Rp. 2,000,000 per month, and the monthly responder spending around Rp. 1.500.000- Rp. 2,000,000. The classification of a prosperous family, namely: disadvantaged families, prosperous families I, II prosperous families, family welfare III, III + and prosperous families. In general, the family life of female workers onion farmer in the village of Tampo can be categorized into a prosperous family II, 2) that the background for working women is the availability of jobs, daily necessities, number of dependents and family health.